THE APPROACHING INFORMATION REVOLUTION AND ITS POSSIBLE IMPLICATIONS FOR RESOURCE SHARING IN CANADA - Pal, Gabriel (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2022)
See PDF